Ress enya a Katherine Walker-Meikle, Medieval cats, Londres, The British Libr ary, 2011, 89 pp. ISBN 978-0-7123-5818-7; i Katherine Walker-Meikle, Medieval pets, Woodbr idge, Boydell and Brewer, 2012, 200 pp. ISBN: 978-1-84383-758-9 - Vicent Baydal Sala (Scripta: Revista Internacional de Literatura i Cultura Medieval i Moderna)
Review to Katherine Walker-Meikle, Medieval cats, Londres, The British Libr ary, 2011, 89 pp.ISBN 978-0-7123-5818-7; & Katherine Walker-Meikle, Medieval pets, Woodbr idge, Boydell andBrewer, 2012, 200 pp. ISBN: 978-1-84383-758-9